Optimizing Routes Quality and Scattering in the AODV Routing Protocol - Guezouri, Mustapha (2007)
An ad-hoc mobile network is a collection of mobile nodes that are dynamically and arbitrarily located in such a manner that the interconnections between nodes are capable of changing on a continual basis. Routing protocols are used to discover routes between nodes. Many mobile ad-hoc networks protocols such as AODV construct route only when desired by the source node (reactively). The advantage hereof is that no prior assumptions of the network topology are required. In highly mobile networks this is an attractive property. Other used protocols (such as OLSR) are said proactive. Such protocols maintain information about routes to all destinations all times. The consequence of this approach is that the amount of control traffic is independent of the actual traffic and mobility in the network. In this paper we describe three major optimization schemes for the well-known AODV routing protocol in order to get some of the proactive protocols features in it. The targeted characteristics are: traffic independent control and shortest path routes.